Ответы 1

  • 1)(9 * c - 7 * k ) ^ 2 = ( 9 * с ) ^ 2 - 2 * 9 * c * 7 * k + ( 7 * k ) ^ 2 = 81 * c ^ 2 - 126 * c * k + 49 * k ^ 2; 2 )(7 * b + 6 * c ) ^ 2 = ( 7 * b ) ^ 2 + 2 * 7 * b * 6 * c + ( 6 * c ) ^ 2 = 4 9 * b ^ 2 + 84 * b * c + 36 * c ^ 2 ; 3) ( 3 * d + 4 ) ^ 2 - 1 = ( 3 * d ) ^ 2 + 2 * 3 * d + 4 ^ 2 - 1 = 9 * d ^ 2 + 6 * d + 16 - 1 = 9 * d ^ 2 + 6 * d + 15.
    • Автор:

      tucker
    • 4 года назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years